Unloading Groove Optimization and the Inner Flow-field Simulation Analysis of the Variable Displacement External Gear Pump - Gao Jiahe; Wang Yansong; Zhao Lihui; Guo Hui; Li Jinguo (Jixie chuandong)
A CFD model of a variable displacement external gear pump is established.The quantitative analysis method is applied to analyze characteristics of the pump inner flow field.The accuracy of the established model is verified by comparing the flux simulated and corresponding tested data.The tooth width formula of gear meshing is obtained.Through oil pressure analysis in the trapped oil area,an optimization scheme with a wedge-shape unloading groove added at the upper piston of the driven gear is proposed,which effectively reduces the pressure fluctuation of trapped oil area.The study results show that,under the condition of the same pump flux,the optimized unloading groove can reduce the pressure fluctuations in the suction and discharge chambers by 12.3% and 8%,respectively.The work is helpful for design and development of the variable displacement external gear pump.